Effect of Thickness and Temperature of SiO2 Layer on Leakage Currents in MOS Capacitor Materials with High Dielectric Constant by Involving the Charge Trap - Fatimah A. Noor; Masturi Masturi; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Jurnal ILMU DASAR, 2014)
Modeling of the leakage current in a field-effect transistor metal-oxide-semiconductor (MOSFET) with high dielectric material has been developed by taking into account the effect of charge traps formed at the interface of high-k material/SiO2. Transmittance calculated using Airy wave function approach and involving the anisotropic electron mass and the effect of coupling between transverse and longitudinal energy represented by the speed of the electrons in the metal gate. Transmittance obtained is then used to calculate the leakage current in the structure of n+Poly-Si/HfSiOxN/trap/SiO2/p-Si for oxide voltage variations, temperature, and thickness of the SiO2. From the calculation that the leakage current decreases with decreasing of oxide voltage and increasing of the thickness of the oxide layer of SiO2. Also obtained that the temperature of the device does not give a great influence on the change of leakage current. Keywords: Leakage current, electron speed, charge traps